1990
DOI: 10.1017/s0021859600075791
|View full text |Cite
|
Sign up to set email alerts
|

Storage root quality in sugarbeet in relation to nitrogen uptake

Abstract: SUMMARYThe relationships between the amounts of nitrogen fertilizer applied and taken up by sugarbeet crops and the concentrations of sugar and α-amino-N in the storage root were examined using data obtained from fertilizer-response trials on different soils in the UK and Belgium between 1974 and 1985. On unmanured mineral soils, crop uptakes of N without fertilizer ranged from 65 to 190 kg/ha and increased linearly with the amount of fertilizer N applied. On organic soils or mineral soils that had received la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 10 publications
2
21
0
2
Order By: Relevance
“…This would be in line with the results of Shock et al [62], who found a negative relationship between nitrate concentration in petioles and polarization (albeit only for one of the two years of their study); with Pocock et al [63], who reported that late additions or releases of nitrogen from soil organic matter reduced the sucrose content; and with Draycott and Christenson [64] and Malnou, Jaggard and Sparkes [40], who indicated that an amount of nitrogen above the optimum had a negative effect on sugar yield. Gordo-Ingelmo [17] explained that beet reacts to nitrogen fertilization increases with a greater development of the leaves and roots, which can cause excessive consumption of sucrose and an increase of non-sugars.…”
Section: Nitrogen Content In Leaves Total Nitrogen Absorption and Casupporting
confidence: 90%
“…This would be in line with the results of Shock et al [62], who found a negative relationship between nitrate concentration in petioles and polarization (albeit only for one of the two years of their study); with Pocock et al [63], who reported that late additions or releases of nitrogen from soil organic matter reduced the sucrose content; and with Draycott and Christenson [64] and Malnou, Jaggard and Sparkes [40], who indicated that an amount of nitrogen above the optimum had a negative effect on sugar yield. Gordo-Ingelmo [17] explained that beet reacts to nitrogen fertilization increases with a greater development of the leaves and roots, which can cause excessive consumption of sucrose and an increase of non-sugars.…”
Section: Nitrogen Content In Leaves Total Nitrogen Absorption and Casupporting
confidence: 90%
“…Accumulation of harmful N ( α ‐amino N) is also favoured by increased N supply (Winter 1998), a finding confirmed by our results in eight of 12 trials. Amino‐N is the organic form of N which is used by sugar beets for their regrowth (Pocock et al. 1990).…”
Section: Discussionmentioning
confidence: 99%
“…1990). Uptake of N by sugar beet crop is related to N availability in soil and results in increased α ‐amino N concentrations in roots (Pocock et al. 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The amino N concentration, and often as an accompanying ion, the sodium concentration, increases, so root quality decreases (Fig. 6) (Pocock and Armstrong 1990;Bell et al 1992;Allison et al 1996). As no interaction between variety and N application occurs, varieties with a high concentration of amino N or betaine have a relatively higher concentration irrespective of the N availability and environmental conditions (Hoffmann 2005).…”
Section: N Fertiliser Applicationmentioning
confidence: 99%